Bibliotekarz – partnerem wspierającym pracowników naukowych i dydaktycznych w Politechnice Lubelskiej - Pomorska-Kowalczyk, Anna; Wójcik, Justyna (Biblioteka Uniwersytecka w Poznaniu, 2018)
W bibliotekach akademickich w ramach działalności statutowej podejmowanych jest wiele przedsięwzięć wspierających naukę i dydaktykę. Organizowany jest warsztat pracy naukowej, dokumentowany jest dorobek naukowy. Biblioteki zaangażowane są również w prace związane z oceną parametryczną jednostek naukowych oraz coraz częściej włączane są w działalność wydawniczą uczelni. Prowadzą też własną działalność dydaktyczną. Poza regularnymi zajęciami dla studentów z zakresu wiedzy o zasobach i usługach biblioteki oraz informacji naukowej organizowane są seminaria z zakresu parametryzacji, open access i prawa autorskiego dla kadry naukowej. Autorki, na przykładzie działalności biblioteki Politechniki Lubelskiej, podjęły próbę przedstawienia roli biblioteki naukowej w funkcjonowaniu uczelni.

In university libraries, there are a lot of Project undertaken which support science and education All within statutory activities the libraries create a proper working environment for scientists and their acquis is documented. The libraries are also engaged in the works on parametric evaluation of faculties. More and more often, they are also included in university publishing. They are also conducting their own didactic projects. Apart from classes for students treating about library resources and services as well as information literacy, there are also additional seminars organized on parametrics, Open Access and author’ rights for university staff. The authors of this papers have tried to analyse the role of a university functioning, based on the example of the Library of University of Technology in Lublin.
A librarian as a supporting partner for researchers and faculty members in Lublin Technical University
Keywords: działalność dydaktyczna biblioteki; library didactic activities; wsparcie dla nauki; library educational activities; wsparcie dla uczelni; support for science; organizacja warsztatu pracy naukowej; organizing proper working; biblioteka akademicka; university library; rola biblioteki naukowej; role/ function of a research library; Biblioteka PL; library of Lublin Technical University; support for university; environment for researchers